Perancangan Sistem Prediksi Keuangan Menggunakan Moving Average Dan Prototype Method - darmawan, terrano windrianto (UNIVERSITAS RAHARJA, 2025)
The significant development of the construction sector in Indonesia requires sophisticated and accurate financial management systems. This research aims to design a web-based financial prediction system for PT. Las Duco Jaya using Moving Average algorithm and Prototype method. The research background is the urgent need for digital transformation in financial management, particularly in construction companies still using conventional recording methods. The research methodology employs a quantitative approach with stages of literature study, field observation, and web-based prototype system development using PHP Laravel and MySQL. The Simple Moving Average (SMA) algorithm is implemented to perform quarterly financial predictions by calculating historical averages. Research results demonstrate the system's ability to generate financial predictions with an accuracy rate of 85-92%, featuring multi-level user authentication, predictive analytics modules, and comprehensive reporting mechanisms. Blackbox testing validated the entire system's functionality, proving its reliability and effectiveness in supporting digital financial management. The research concludes that this financial prediction system is more than just a recording tool; it is a strategic partner empowering organizations to understand and control financial dynamics with high precision. The study suggests continuous development, improvement of prediction algorithms, and integration of cutting-edge technologies to optimize system performance in the future